Pemanfaatan Konten Kecantikan di Youtube oleh Remaja Siswi (Studi Kasus di SMA Angkasa 2 Jakarta Timur) - Fadhila Ayuningtyas; Agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Social media, which was previously only used to communicate with other people, has now created a new phenomenon as a place or place for us to find and see the latest information about beauty. One of the social media that is often used today is Youtube. The focus in this research is to find out more, how to use beauty content on Youtube by teenage students at SMA Angkasa 2 East Jakarta by utilizing the beauty content on YouTube social media. This study uses a qualitative research approach with descriptive research type. This research data collection technique is in the form of in-depth interviews and documentation. Based on data analysis, the researchers obtained the following results, (1) Youtube is used as a source of information for beauty reviews, (2) Youtube is used as a reference for make-up to support appearance, (3) Helping women to find beauty treatments right.